Generational Differences in Nursing Students' Perceptions of Faculty Caring Behaviors and Presence in Online Registered Nurse to Bachelor of Science in Nursing Programs. - Macario, Kimberly Cardaci (International Journal for Human Caring, 2025)
Abstract: The purpose of this study was to explore how students of different generations perceived presence and caring behaviors by faculty in online Registered Nurse to Bachelor of Science in Nursing programs. Results showed that millennials reported statistically significant higher perceptions of social presence when compared with nonmillennials. Although generation was not a predictor of caring, all presence subscales were positively and significantly correlated with the total caring score. Teaching presence was a significant predictor of students' perceptions of caring in online courses.
Place: New York, New York
Keywords: Adult; Adult: 19-44 years; Age Factors; Caring Evaluation; Colleges and Universities; Conceptual Framework; Convenience Sample; Correlational Studies; Descriptive Research; Descriptive Statistics; Education; Non-Traditional; Education; Nursing; Baccalaureate; Educational Measurement; Exploratory Research; Faculty; Nursing; Faculty-Student Relations; Human; Intergenerational Relations; Learning Environment; Middle Age; Middle Aged: 45-64 years; Nursing Practice; Evidence-Based; Presence; Professional-Patient Relations; Program Evaluation; Quantitative Studies; Questionnaires; Registered Nurses Psychosocial Factors; Regression; Social Behavior Evaluation; Statistical Significance; Student Attitudes Evaluation; Students; Nursing Psychosocial Factors; Summated Rating Scaling; Teaching Methods; United States; dept.nur